1.7(z+7)-(7.6+0.7z)=-7+2

Simple and best practice solution for 1.7(z+7)-(7.6+0.7z)=-7+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.7(z+7)-(7.6+0.7z)=-7+2 equation:


1.7(z+7)-(7.6 + 0.7z)=-7+2

We simplify the equation to the form, which is simple to understand
1.7(z+7)-(7.6 + 0.7z)=-7+2

Reorder the terms in parentheses
+(+1.7z+11.9)-(7.6 + 0.7z)=-7+2

Remove unnecessary parentheses
+1.7z+11.9-(+7.6 + 0.7z+)=-7+2

Remove unnecessary parentheses
+1.7z+11.9-7.6-0.7z=-7+2

We move all terms containing z to the left and all other terms to the right.
+1.7z-0.7z=-7+2-11.9+7.6

We simplify left and right side of the equation.
+1z=-9.3

We divide both sides of the equation by 1 to get z.
z=-9.3

See similar equations:

| -4=m-3-3 | | 11+9x+15x+5=60 | | 625=5x^3 | | 0.25(12+4s)-0.5(6+2s)= | | 3(2x+6)= | | x+23+x+51=168 | | 168+x+23=x+51 | | -2(u+3)-3(u+5)= | | 0.3+0.2(10)=0.1(x+40) | | 19-19x=14-9x-[25+10x] | | 19-19=14-9x-[25+10x] | | -8t+12=4t+48 | | 3x=x+15 | | 9x+6=3x+4 | | 19-19=14-9x-[375+10x] | | 2x+3g=21 | | 3(4k+5)-19k+9+2= | | r^2+2r-12=0 | | 2(n-4)=3n-4 | | .06(a+200)+.1a=172 | | 5+3z= | | 3.6x+.9=8.8-1.5x | | 6(2x-4)=3(-x+7)+9x | | 8x+3=10x-7 | | 92+7x+9=6+4x | | 35x^2+5x=0 | | 5x^2+7x-11=0 | | 5x^2+7x+11=0 | | 13t+t^2+36= | | 4x+7=-1(x-3) | | 4-4(x+5)=7x-16 | | 4x+7=x-(x-3) |

Equations solver categories